Freeze-Thaw Pretreatment Can Improve Efficiency of Bacterial DNA Extraction From Meconium - Xin, Yuntian; Xie, Jingxian; Nan, Bingru; Tang, Chen; Xiao, Yunshan; Wu, Quanfeng; Lin, Yi; Zhang, Xueqin; Shen, Heqing (Frontiers in Microbiology, 2021)
Although the presence of live microbes in utero remains under debate, newborn gastrointestinal bacteria are undoubtedly important to infant health. Measuring bacteria in meconium is an ideal strategy to understand this issue; however, the low efficiency of bacterial DNA extraction from meconium has limited its utilization. This study aims to improve the efficiency of bacterial DNA extraction from meconium, which generally has low levels of microflora but high levels of PCR inhibitors in the viscous matrix. The research was approved by the ethical committee of the Xiamen Maternity and Child Health Care Hospital, Xiamen, China. All the mothers delivered naturally, and their newborns were healthy. Meconium samples passed by the newborns within 24 h were collected. Each sample was scraped off of a sterile diaper, transferred to a 5-ml sterile tube, and stored at -80 °C. For the assay, a freeze-thawing sample preparation protocol was designed in which a meconium-InhibitEX buffer mixture was intentionally frozen one to three times at -20 ℃, -80 °C, and (or) in liquid nitrogen. Then, DNA was extracted using a commercial kit and sequenced by 16S rDNA to verify the enhanced bacterial DNA extraction efficiency. Ultimately, we observed the following. (1) 30 mg lyophilized meconium was the optimal amount for DNA extraction. (2) Freezing treatment for 6 h improved DNA extraction at -20 °C. (3) DNA extraction efficiency was significantly higher with the immediate thaw strategy than with gradient thawing at -20 ℃, -80 ℃, and in liquid nitrogen. (4) Among the conditions of -20 °C, -80 °C, and liquid nitrogen, -20 °C was the best freezing condition for both improving DNA extraction efficiency and preserving microbial species diversity in meconium, while liquid nitrogen was the worst condition. (5) Three freeze-thaw cycles could markedly enhance DNA extraction efficiency and preserve the species diversity of meconium microflora. We developed a feasible freeze-thaw pretreatment protocol to improve the extraction of microbial DNA from meconium, which may be beneficial for newborn bacterial colonization studies.